Electoral violence in Africa’s shrinking civic space: Nature, magnitude and remedies - Timilehin Olayinka Omoniyi (Journal of Governance and Accountability Studies, 2026)
Purpose: This study investigates the nature, magnitude, and potential remedies for electoral violence in Nigeria, Ghana, and Kenya, with the aim of offering evidence-based insights for mitigating its occurrence. Methods: A descriptive survey design was adopted. Data were collected using the Comprehensive Electoral Violence Questionnaire (r = 0.82), which was developed to measure stakeholders’ perceptions of electoral violence. A total of 1,800 participants (600 from each country) responded to items addressing the nature, scale, and possible solutions to electoral violence in the three countries. Results: The findings revealed that the most prominent features of electoral violence include poor civic education, the misuse of state resources by incumbent governments, and the influence of foreign actors. The magnitude of violence is reflected in the widespread use of firearms, the involvement of large, organized groups, and the targeting of specific ethnic or religious communities. Key remedies identified were ensuring judicial independence for peaceful resolution of disputes, promoting civic education, and strengthening electoral commissions. Conclusions: Electoral violence in Africa is multifaceted, deeply rooted in governance weaknesses, and exacerbated by systemic and external factors. Addressing this requires institutional reforms, public education, and impartial legal mechanisms. Limitations: The study relied solely on self-reported data from selected stakeholders, which may have introduced perception bias and limited generalizability. Contributions: This study offers comparative insights into three African democracies and provides actionable policy recommendations for reducing electoral violence and strengthening democratic resilience.